Pengaruh Bokashi Tandan Kosong Kelapa Sawit (TKKS) dan NPK Grower terhadap Pertumbuhan Bibit Tanaman Kakao (Theobroma cacao L.) - Hutauruk, Tri Agung Horas; Zahrah, Siti (UIR PRESS, 2026)
The aim of the study was to determine the interaction and main effect of bokashi palm empty fruit bunches (EFB) and NPK grower on cocoa plant nurseries. It has been carried out in the experimental garden of the Faculty of Agriculture, Riau Islamic University. This research was conducted for 4 months starting from December 2021 to March 2022. The design used in this study was a Completely Randomized Factorial Design consisting of 2 factors. The first factor was the dose of bokashi palm oil empty fruit bunches (EFB) (B) consisting of 4 levels namely 0, 30, 60, 90 grams per polybag and the second factor was the dose of NPK Grower fertilizer (N) consisting of 4 levels namely 0, 3, 6.9 grams per polybag, each treatment combination consisted of 3 replications. Parameters observed were plant height, number of leaves, stem diameter, root volume, widest leaf area. Observational data were analyzed for variance (Test F). If the calculated F is greater than the F table, then it is continued with a further test of the Honest Significant Difference (HSD) at the 5% level. The results showed that the interaction effect of the combination of bokashi OPEFB and NPK Grower was significant for all observation parameters. The best treatment was the combination of 90 g/polybag bokashi OPEFB and NPK Grower 9 g/polybag (B3N3). The main effect of OPEFB bokashi is real on all observation parameters. The best treatment was found in the OPEFB bokashi treatment 90 g/polybag (B3). The main effect of NPK Grower is real on all observation parameters. The best treatment was found in the NPK Grower 9 g/polybag (N3) treatment.